Morphometrical study of sacral hiatus in dry human sacra - Parashuram, Rajapur (International Journal of Research in Medical Sciences, 2017)
Background: The sacral hiatus is the site for caudal epidural anaesthesia during perineal surgery and also for a painless delivery. It is also used for three dimensional colour visualization of lumbosacral epidural space in orthopaedic practice for diagnosis and treatment. Sacrum is one of the bones which exhibit variations. Therefore the importance of the normal sacral hiatus and its variations is of great clinical significance. The reliability of caudal epidural anaesthesia is 70% - 80% in the literatures. The objective of the study was to examine, measure and record the morphometry of sacral hiatus under the following headings in order to study the anatomical variations which would be useful for caudal epidural anaesthesia and improve the reliability of the same. a) Shape of sacral hiatus, b) level of apex, c) level of base, d) length of the sacral hiatus, e) transverse width at the base, and f) anteroposterior depth at the apex. Methods: A total of 200 dry, complete, undamaged human sacra of unknown sex were used in this study. Measurements were taken using vernier calipers. In this study six parameters were taken. All the readings were tabulated and subjected to analysis. Results: Various shapes of sacral hiatus were observed which included Inverted-U (50%), Inverted-V (27.5%), Irregular (15.5%), Dumb bell (2%), and Bifid (2%). The mean anteroposterior depth of sacral canal at the level of apex of sacral hiatus was 4.25mm. The mean length of sacral hiatus was 19.63 mm and the mean transverse width of sacral hiatus at the level of base was 11.42 mm. There was complete spina bifida in 4 (2%) and absence of sacral hiatus in 2 (1%) cases. Conclusion: The sacral hiatus has anatomical variations. Understanding of these variations may improve the reliability of caudal epidural anaesthesia.